I will blossom anyway : a novel - Bose, Disha (Ballantine Books, 2025)
"Durga is named after the Bengali goddess, pure of heart, filled with goodness. But the goddess has an alter-ego--fearless Kali, of fire and crackling with energy. The third of four children born to a middle-class Kolkata family, quiet Durga is surprisingly the first to leave the nest of her loving, overbearing family. She is not as charming as her older sister, Tia, as lighthearted as her brother, Arjun, or as clever as her younger sister, Parul. But when she arrives in Ireland to work at a tech company, she finds that for the first time ever she is free--to have fun, to stay out, to sample everything that life has to offer. Suddenly, Durga can be whoever she wants to be. And she wants it all. But freedom comes at a price. Durga falls in love with handsome, charismatic Jacob, and grows close with his sister, Joy, now Durga's flatmate, and best friend. But when Jacob breaks up with Durga, she's unmoored. Who will she choose to be: fearless Kali or peace-loving Durga? Will she stay in Ireland with her newfound identity and livelihood, or will she return to India, where she is comfortable? Perhaps neither option is enough. Durga must summon her inner Kali, the brave and fearless warrior, and fight for the life she truly desires"--